African Spilogona Schnabl: morphology of the male terminalia and description of a new species (Diptera: Muscidae) - Couri, Márcia S.; Pont, Adrian C. (Zootaxa, 2017)
Spilogona breviaristata sp. nov. from South Africa is described and the morphology of the male terminalia of seven African Spilogona Schnabl (Diptera, Muscidae) species are described and illustrated: Spilogona biguttata Emden, Spilogona fuscotriangulata Emden, Spilogona natalensis Zielke, Spilogona pertinisetodes Emden, Spilogona quasifasciata Emden, Spilogona semifasciata Emden and Spilogona spinipes (Bigot). The material studied is deposited in the Natural History Museum (BMNH), London, United Kingdom, and paratypes of the new species are also in the Museu Nacional, Universidade Federal do Rio de Janeiro (MNRJ), Rio de Janeiro, Brazil, and the Oxford University Museum of Natural History (OUMNH), Oxford, United Kingdom.